Relational Anthropology for Contemporary Economics A Multidisciplinary Approach - van Nes, Jermo; Nullens, Patrick; van den Heuvel, Steven C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This open access book offers a multidisciplinary dialogue on relational anthropology in contemporary economics. A particular view of the human being is often assumed in economic models, but seldom acknowledged let alone explicated. Addressing this neglected area of research in economic studies, altogether the contributors touch upon the importance and potential of virtues, the notions of freedom and self-love, the potential of simulation models, the dialectics of love, and questions of methodology in constructing a relational anthropology for contemporary economics. The overall result is a highly informative and constructive dialogue, establishing inter alia a research agenda for future collaborative and multidisciplinary study.
Chapter 1. Introduction -- Chapter 2. Towards a Relational Anthropology Fostering an Economics of Human Flourishing -- Chapter 3. Natural Goodness -- Chapter 4. Homo Amans: A Personalist Response -- Chapter 5. God$1 (Bs Work in the World: The Deep Compatibility of Real Liberalism with Any Abrahamic Religion -- Chapter 6. What Is the Nature of Christian Love? Homo Amans and Revolutionary Altruism -- Chapter 7. Searching for the Anthropological Foundations of Economic Practice: Controversies and Opportunities -- Chapter 8. Altruistic Concern for the Other and the Development of the Virtue of Humility -- Chapter 9. Trust, Faith, and Social Imaginary: Prolegomena to an Anthropology of Personhood -- Chapter 10. Homo amans in the Economy: A Utopia? -- Chapter 11. Out with the Old, In with the New? From Conceptual Reconstruction in Philosophical Anthropology to a Realistic Theory of Change -- Chapter 12. Personal Leadership: How to Change What Cannot Be Changed: A Response to Wesley Wildman$1 (Bs Out with the Old, In with the New? -- Chapter 13. A Relational Anthropology for Contemporary Economics? Concluding Reflections.s
Keywords: Philosophy of mind; Self; Economics; Culture; Ethnology; Social sciences; Humanities; Philosophy of the Self; Cultural Economics; Sociocultural Anthropology; Humanities and Social Sciences